About the relationship between people and animals. My Dren by Danko Anđelinović - Dyras, Magdalena (Poznańskie Studia Slawistyczne, 2025)
The article is an attempt to read the novel My Dren (1939) by Danko Anđelinović in the context of ideas spread since the end of the 19th century, and in the strictly scientific field since the 1970s by the creators of animal studies. The author first reviews theoretical works published in Croatia in this trend, and then shows Anđelinović’s autobiographical novel as anticipating animal narratives in Croatian literature.